Cultivo consorciado de milho de segunda safra com espécies de adubo verde visando à diminuição da adubação nitrogenada de cobertura - Gonçalves, Rodrigo Singulane (Universidade Federal de São Carlos, 2018)
Winter corn (second crop corn) has become the main autumn-winter crop in Brazil. In the 2016/2017 crop, the average productivity was 5,303 kg ha-1, surpassing that of the summer corn (first crop corn). With the expectations of increased productivity and expansion of the cultivated area, there will be a need to supplement sowing fertilization with N in topdressing fertilization, a practice often suppressed due to water deficit in the period of extemporaneous cultivation of winter corn. The use of green manure species between the crop row in consortium with winter corn has been recommended to maintain soil moisture. In addition, considering that the N of green manure can become available to the main crop through in vivo mechanisms in intercropping, it is possible to decrease the amount of N offered in topdressing fertilization. The aims of this study were: (i) to evaluate biometric, nutritional, and production parameters of the winter corn (hybrid 30A37 PW), cultivated in consortium with green manure species and with doses of nitrogen in topdressing; (ii) the degree of nitrogen fertilization suppression using green manure. The experiment was installed in a dystrophic Oxisol, with a randomized block design and a 4x3 factorial scheme, with five replicates. The treatments consisted of four conditions for establishing green manure (without green manure; Crotalaria spectabilis; Cajanus cajan; Crotalaria spectabilis + Cajanus cajan;) and three levels of nitrogen topdressing fertilization (0, 15, and 30 kg ha-1 of N ), 30 days after the emergency. Dry mass, stem diameter, plant height, number of leaves above the ear, weight of 1000 grains, number of rows per ear, number of grains per row, grain mass per ear, the mass of the ear without straw, the length and diameter of the ear, the height of insertion of the first ear, productivity, and leaf contents of N, P, K, Ca, Mg and S were evaluated. The treatments did not produce significant differences in biometric and productivity parameters, which were lower than those found in the scientific literature. Regardless of the treatment, leaf N levels were above the range considered adequate for winter corn. Except for the treatment in which Crotalaria spectabilis was grown between the crop row and the addition of 30 kg ha-1 of N in topdressing fertilization, all experimental conditions resulted in insufficient P foliar levels. Experimental plots with no intercropping with green manure resulted in plants with adequate K leaf levels. No insufficient leaf levels of Ca, Mg and S were observed. It was not possible to estimate the degree of nitrogen fertilization suppression for winter corn intercropped with green manure species. The average productivity, which varied from 2.2 to 2.4 t ha-1, was considered very low when compared to the average Brazilian productivity and was attributed to the inadequacy of the 30A37 PW hybrid to climatic zoning, to the deficiencies of P and K and probable Zn insufficiency.
Intercrop of winter corn with green manure species aiming to decrease nitrogen topdressing fertilization
Keywords: Milho safrinha; Crotalaria spectabilis; Cajanus cajan; Híbrido 30A37 PW; Nitrogênio; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO